Multivariate optimization and validation of an analytical methodology by RP-HPLC for the determination of losartan potassium in capsules - Bonfilio, Rudy; Teixeira Tarley, Cesar Ricardo; Pereira, Gislaine Ribeiro; Salgado, Hérida Regina Nunes [UNESP]; de Araujo, Magali Benjamim (Elsevier B.V., 2009)
This paper describes the optimization and validation of an analytical methodology for the determination of losartan potassium in capsules by HPLC using 2(5-1) fractional factorial and Doehlert designs. This multivariate approach allows a considerable improvement in chromatographic performance using fewer experiments, without additional cost for columns or other equipment. The HPLC method utilized potassium phosphate buffer (pH 6.2: 58 mmol L(-1))-acetonitrile (65:35, v/v) as the mobile phase, pumped at a flow rate of 1.0 mL min(-1). An octylsilane column (100 mm x 4.6 mm W., 5 mu m) maintained at 35 degrees C was used as the stationary phase. UV detection was performed at 254 nm. The method was validated according to the ICH guidelines, showing accuracy, precision (intra-day relative standard deviation (R.S.D.) and inter-day R.S.D values <2.0%). selectivity, robustness and linearity (r=0.9998) over a concentration range from 30 to 70 mg L(-1) of losartan potassium. The limits of detection and quantification were 0.114 and 0.420 mg L(-1), respectively. The validated method may be used to quantify losartan potassium in capsules and to determine the stability of this drug. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Doehlert design; Fractional factorial design; Losartan potassium; Reversed-phase chromatography; Validation